(untitled) (Bangladesh Journal of Animal Science, 2020)
This study aimed to analyze the hemato profile of crossbred lactating cows reared at Bangladesh Agricultural University (BAU) Dairy Farm. Thirty-two (32) healthy crossbred lactating cows of Holstein-Frisian (HF), Jersey (J), Sindhi Sahiwal (SS) and Red Chittagong (RCC) were selected for the study and divided into four (04) groups. The cows were allowed to feed and manage according to dairy farm own scheduled-ration. The collected blood samples were analyzed for hematological and biochemical parameters viz. Hemoglobin (Hb), Packed cell volume (PCV), Total leukocyte count (TLC), and Total erythrocyte count (TEC) and Serum urea, Glucose, Albumin, Calcium, and Phosphorus, respectively by using an automated chemistry analyzer. The results revealed that the hematological and biochemical parameters non-significantly (p>0.05) differed between the crossbred groups. From the experiment, the higher amount of Hb (11 g/dL) and PCV (40%) was found in HF and RCC cows, respectively. The TLC was higher in SS and RCC but the TEC was recorded stable along with a slight increment in RCC. As far as the biochemical parameters are concerned, the blood urea concentration was found higher (28 mg/dL) in HF and RCC lactating cows. The same pattern was observed in the case of albumin concentration. On the contrary, the lowest value of Calcium was found in RCC but the Phosphorus concentration showed a little higher in RCC. It can be concluded that the overall herd health was satisfactory based on the blood profile parameters. Bang. J. Anim. Sci. 2019. 48 (2): 139-144